2019
DOI: 10.14218/jcth.2017.00037
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Hepatic Encephalopathy in Indians: Psychometric Hepatic Encephalopathy Score and Inhibitory Control Test for Diagnosis and Rifaximin or Lactulose for Its Reversal

Abstract: Background and Aims: Psychometric hepatic encephalopathy score (PHES) is used widely for diagnosis of minimal hepatic encephalopathy (MHE). This prospective study aimed to determine the utility of the inhibitory control test (ICT) for the diagnosis of MHE. Additionally, the efficacy of rifaximin and lactulose for reversal of MHE was evaluated. Methods: A total of 180 eligible cirrhotic patients underwent testing for MHE. When PHES was # −5 and ICT lures were $ 14, MHE was diagnosed. The 108 patients with MHE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…After duplicates were removed, a total of 48 studies were identified in the present study, of which 36 were excluded from the analysis according to the inclusion and exclusion criteria; the remaining 12 studies 6,9–19 were included in the systematic review (Figure 2). The characteristics of these 12 studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After duplicates were removed, a total of 48 studies were identified in the present study, of which 36 were excluded from the analysis according to the inclusion and exclusion criteria; the remaining 12 studies 6,9–19 were included in the systematic review (Figure 2). The characteristics of these 12 studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of these 12 studies are presented in Table 1. Three 6,10,19 of 12 studies were published before 2010, and nine studies 9,11–18 were published after 2010. All 12 studies 6,9–19 enrolled patients with different etiologies of liver cirrhosis, including viral hepatitis, alcohol hepatitis, autoimmune hepatitis, nonalcoholic steatohepatitis, primary biliary cirrhosis, primary sclerosing cholangitis, and cryptogenic cirrhosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ICT has been used to screen MHE in the United States, Germany, Italy, and India (Table 1 )[ 6 , 8 - 11 , 23 , 24 ]. In the United States, with a cut-off value of ≥ 5 lures/person, Bajaj et al[ 6 ] found that the ICT had a 90% sensitivity and specificity for screening MHE, and the area under the receiver operator characteristic (AUROC) was 0.902 when using the standard paper-and-pencil psychometric tests (SPT) as the reference standard.…”
Section: Inhibitory Control Testmentioning
confidence: 99%